Inventory Control Information Systems With EOQ AND ROP Methods In Sales Of Building Materials In UD. Diqy Pasaman Barat By Applying To The VB Net Programming Language And Mysql Database: Inventory Control Information Systems With EOQ AND ROP Methods In Sales Of Building Materials In UD. Diqy Pasaman Barat By Applying To The VB Net Programming Language And Mysql Database - Nursaka Putra; Ali Akbar Ritonga; Ibnu Rasyid Munthe; Masrizal Masrizal; Muhammad Halmi Dar (Jurnal Mantik, 2020)
Research that has been done at UD. DIQY Pasaman Barat by using field research methodology, library research. analyzing problems in the data processing system inventory products or goods that are running in the UD building shop. DIQY then designed a better system that is expected to improve the efficiency and effectiveness of the work of employees and to design information systems that can produce detailed reports and make it easier to find information when there is the correction of certain data. The design of the Information System for Selling Goods using the VB NET Programming Language will provide a better solution to the problems encountered. The level of error in processing data items and sales transactions can be minimized because the new system can speed up and simplify the administration in making reports, to produce accurate information.